Production of Andropogon gayanus cv. Planaltina dry matter estimated through NDVI - Dias, João Lucas Aires; Pereira, Paulo Alexandre Rodrigues; Barros, Izaías de Macedo; Barros, Pedro Matheus Barboza; Silva Neto, Sabino Pereira da (Revista Agrogeoambiental, 2020)
Pasture management studies seldom use remote sensing, especially for Andropogon gayanus cv. Planaltina. This work aimed to investigate whether a single-chip digital camera converted into multispectral equipment could measure and perceive differences in the normalized difference vegetation index (NDVI) in Andropogon gayanus cv. Planaltina grass subjected to different doses of nitrogen. In a greenhouse with a randomized block design, the research team subjected the cultivar to 5 different doses of nitrogen (treatments), with four replications. The group compared the NDVI measurements of canopies carried out with a GreenSeeker® HCS-100 active optical sensor and a Canon PowerShot A495 single-chip camera that was converted into a multispectral device by replacing the glass filter that blocks the passage of the infrared by a filter that allows the passage of the red and near infrared wavelengths. Both measurements were correlated with nitrogen doses, stem and leaf blades dry matter and dead material production, and cultivar height. The study concluded that the multispectral camera, as well as the active optical sensor, measured the NDVI and noticed differences in the production of stem, leaf blades and dead material dry matter, and Andropogon gayanus cv. Planaltina plant height when subjected to different doses of nitrogen.